MANAGEMENT OF THE MAIN ULCER OF THE LOWER LIMBS BY THE STOMATHERAPIST NURSE - Claudia Rodrigues da Silva, Ana (Health and Society, 2023)
Lower limb ulcers constitute a serious worldwide social and collective health problem, affecting the user, arising spontaneously or accidentally, usually evolving into a chronic injury, accompanied by other preventable injuries. In Brazil, among lower limb ulcers, venous ulcers are the most prevalent, constituting 70% to 90% of ulcers, followed by 10% of arterial ulcers. The incapacity that generates the injury is worrying, since it leads to several changes and affects the quality of life. The general objective of this research is to point out the main etiologies of lower limb ulcers based on the literature. The specific objectives consist of presenting the characteristics of these injuries and the role of the stomal therapist nurse in managing them. The justification for this work is based on the increasing rates of complications of Diabetes Mellitus that generate ulcers and for better academic updating of health professionals in stomatherapy who also carry out continuing education with their patients and families. The research methodology was a bibliographic review and the databases consulted: SCIELO and BVS. Complete articles available online for free, from studies carried out with samples of patients of all ages, published between 2015 and 2020, written in Portuguese, Spanish and English, were included. Most of the studies presented pointed out the comorbidities: obesity, diabetes mellitus and arterial hypertension as conditions for the worsening of the patient’s condition and the interference in the healing process of the ulcer. Thus, the great challenge for nursing, especially for nurses, is the planning and implementation of care for patients with ulcers in the lower limbs.